Analysis of Cubic Boron Nitride Single Crystal Defects Growth under High Temperature and High Pressure - Lichao Cai; Bin Xu; Meizhe Lv; Feng Jia; Xingdong Yuan (Journal of Chemistry)
Cubic boron nitride (cBN) single crystals are synthesized under high temperature and high pressure in the Li-based system. The growth defects on hexagonal and triangular (111) surfaces of cBN single crystals after rapid cooling are discussed systemically for the first time using the atomic force microscope. Some impurity particles, triangle cone hole defects, lamellar-fault structures, and big steps are obvious on the surfaces of cBN single crystals. The formation mechanism of these defects is analyzed briefly at the synthetic process of cBN single crystals, and the growth mechanism of cBN single crystals transform from the two-dimensional growth to dislocation growth mechanism under high temperature and high pressure.